2004
DOI: 10.1074/jbc.m408011200
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin 2 Catalyzes the Reversible Oxidation and Glutathionylation of Mitochondrial Membrane Thiol Proteins

Abstract: The redox poise of the mitochondrial glutathione pool is central in the response of mitochondria to oxidative damage and redox signaling, but the mechanisms are uncertain. One possibility is that the oxidation of glutathione (GSH) to glutathione disulfide (GSSG) and the consequent change in the GSH/GSSG ratio causes protein thiols to change their redox state, enabling protein function to respond reversibly to redox signals and oxidative damage. However, little is known about the interplay between the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
355
0
4

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 372 publications
(369 citation statements)
references
References 51 publications
(79 reference statements)
10
355
0
4
Order By: Relevance
“…1A). This result is basically consistent with those reported in the literature (13,14). The 51 kDa subunit was specifically involved in the above redox modification when the Fp subcomplex was exposed to GSSG (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…1A). This result is basically consistent with those reported in the literature (13,14). The 51 kDa subunit was specifically involved in the above redox modification when the Fp subcomplex was exposed to GSSG (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…This result was further verified by immunoblotting as reported by Beer et. al (13). However, the molecular mechanism of the above redox event remains unclear and needs to be defined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although glutathionylation of PTP1B can be achieved in vitro with the purified enzyme through oxidation by H 2 O 2 and addition of GSH (through the sulfenic acid and sulfenyl-amide as described above) (26) (27) or by addition of a very high concentration of GSSG (63), it is not known if glutathionylation occurs enzymatically or non-enzymatically in vivo and kinetic considerations clearly argue against the latter (87). While formation of glutathionylated PTP1B through disulfide exchange in the cytosol by reaction with GSSG enzymatically or non-enzymatically is unlikely due to the requirement for markedly increasing GSSG, a recent paper by Beer et al demonstrated glutaredoxin 2 dependent catalysis of glutathionylation/deglutationylation of mitochondrial proteins (88). Interestingly, a paper by Seth and Rudolph of recent publication extended the diversity of mechanisms utilized by PTPs to prevent irreversible oxidation of the active site.…”
Section: A Signaling Proteins In Which Critical Cysteines Are Modifiedmentioning
confidence: 99%